Gender Differences in the Earnings Mobility of Migrants - Regina Flake (LABOUR, 2013)
This study analyses gender differences in the intergenerational earnings mobility of second-generation migrants in Germany. Thereby it takes into account the influence of assortative mating and the parental integration. First, intergenerational earnings elasticities are estimated at the mean and along the earnings distribution. The results do not reveal large differences in the mobility â neither between natives and migrants nor between men and women. Second, intergenerational changes in the relative earnings position are analysed. These results confirm that migrants are mostly as (im)mobile as the native population.
Keywords: 330; F22; J12; J30; J62